An Investigation Into Form Two Students’ Perceptions of Their Parents’ Involvement in Their Education Both Pre and Post Their SEA Examinations - O’Neil-Kerr, Odette (My University, 2014)
This study investigated students’ perceptions of their parents’ involvement in their education both pre and post their SEA examinations. Data were collected through interviews with six Form 2 students, and sought to determine their perceptions of how sustained the parental involvement was, and the impact that this involvement had on their performance. Other data were collected through document analysis. Emergent themes from the study were: 1) relationship with mother and father, 2) relationship between parents and teachers, 3) parental involvement in primary school, 4) parental involvement in secondary school, and 5) students’ expectations of parental involvement. The findings indicated that there was a decline in the depth of parental involvement as the students moved from the primary to the secondary school. Although the parents were still involved and showed an interest in their children’s schooling, their involvement was more of a guiding nature than a hovering nature.
Keywords: Secondary school students; Student attitudes; Primary education; Secondary education; Parent participation; Perceptions; Parent student relationship; Case studies; Trinidad and Tobago